Analysis of Path Loss In 802.11ac Data Communication at 5.8 Ghz Frequency in Padang City - YULISWAR, TEDDY; Elfitri, Ikhwana; W purbo, Onno (P3M Politeknik Negeri Bengkalis, 2024)
This research aims to analyze path loss in data communication using the 802.11ac standard at a frequency of 5,185 MHz in the city of Padang. We collected data on environmental parameters, including air temperature ranging from 24.44°C to 31.11°C, relative humidity between 77% and 96%, dew point from 24.4°C to 26.11°C, and wind speed, over a period of four consecutive weeks. Additionally, we measured technical network parameters like signal strength, noise, and throughput at a 1.5 km distance between two towers, each measuring 28 meters and 25 meters in height. Environmental conditions, particularly humidity and wind speed, influence path loss, according to the research results. In the measurement, the received signal varies from -44 dBm to -49 dBm, while the noise is in the range of -90 dBm to -92 dBm. The throughput generated also varies between 259.2 Mbps and 295.2 Mbps. We discovered that high humidity and low wind speed lead to an increase in throughput, suggesting that weather conditions influence the quality of data transmission. This research provides important insights into the planning and optimization of 802.11ac wireless networks in urban areas, particularly for improving service quality under various environmental conditions